TRPM6 Gene Mutation Responsible for Familial Hypomagnesemia with Secondary Hypocalcemia - Hussein, Mahmoud Al; Saleh, Shafiqa; Doory, Sura El; Sabbah, Mohammed Ali Al; Saleh, Maysa (Archives of Clinical and Medical Case Reports, 2019)
This case report describes a five years old Emirati boy, who had a history of convulsions (twice) at the age of two weeks, associated with reduced activity and excessive startling response. His investigation showed hypomagnesemia with normal calcium level, normal parathyroid hormone and no urinary loss of Magnesium (Mg). Mutations in the TRPM6 gene, a member of the transient receptor potential family of cation channels, was identified by the genetic study. This gene, located on chromosome 9, is expressed in the intestinal epithelium and renal cells. TRPM6 gene plays a crucial for magnesium homeostasis which is subsequently linked to the rare metabolic disorder; Familial hypomagnesemia with secondary hypocalcemia.